Flexible Work Arrangements Program Implementation Evaluation - Sa, Yongjin (Advances in Social Sciences Research Journal, 2021)
This research primarily focuses on construction of the program evaluation proposal for the flexible work arrangements. In order to make the program evaluation design, this paper specifically discusses evaluation questions and data collection analysis regarding three kinds of evaluations including needs assessment, implementation evaluation, formative evaluation, and summative evaluation. Furthermore, the expected positive effects and main functions of the flexible work arrangements program evaluation are also suggested.